Negotiating the tangible and the intangible:: A case for street art festivals - Bhasin, Aparajita (SAUC - Street Art and Urban Creativity (repository), 2017)
Street art in the past decade or so has witnessed development in the form of the street art festivals that have sprung up across the globe. These festivals bring artists, street art enthusiasts, art historians, and the public together in the celebration and creation of street art. Practicing art in this format can arguably be seen as replacing the art institutions that often attempt to represent and commercially engage with this art, thus proving to be antithetical to its systems. Street art is characterised by an inherent contradiction that lies within it – while on one hand it is tangible due to its unregulated availability to people for aesthetic experience, both visually and physically, it is also intangible due to its ephemerality and unstructured manner of recording history. This article makes a case for street art festivals as representation of what may be called a ‘Street art world,’ that allows for documentation and reflection of the art movement that began in the late 1960s and the 1970s.